Advertisement for Dow Aromatics - Dow Chemical Company (1942)
Color print advertisement for Dow Aromatics. The advertisement features a mixed imagery illustration of a woman's face, a dancing couple, a hand holding a bar of soap, white roses, a perfume bottle, a beaker and a seated bull smelling a bouquet of flowers (a possible reference to the children's book The Story of Ferdinand, published in 1936). The accompanying text describes Dow Chemical's work in the field of synthetic aromatic chemicals and flavorings. The text also notes that Dow is developing synthetic food flavors to replace materials that are no longer widely available. Notably, the advertisement was produced during World War II and bears the Company's wartime tagline "Dow: Chemicals Indispensable to Industry and Victory."
Keywords: Dow Chemical Company; Advertising; Corporations; Chemical industry; Perfumes; Perfumes industry; Perfumes, Synthetic; Women in advertising; World War (1939-1945); Advertising, Industrial